2021
DOI: 10.1093/cvr/cvab331
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological pathways in patients with heart failure and atrial fibrillation

Abstract: Aims Atrial fibrillation (AF) and heart failure (HF) are two growing epidemics that frequently co-exist. We aimed to gain insights into underlying pathophysiological pathways in HF patients with AF by comparing circulating biomarkers using pathway overrepresentation analyses. Methods and Results From a panel of 92 biomarkers from different pathophysiological domains available in 1,620 patients with HF, we first tested which b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…WFDC2 (also known as HE4)—a profibrotic protease inhibitor with a potential role in natural immunity 17 —emerged as the strongest proteomic predictor of heart failure. Previous research in hospitalized heart failure patients demonstrated associations of circulating WFDC2 with disease severity as well as kidney function 30 . As WFDC2 is expressed exclusively in non-cardiovascular tissues such as the respiratory tract, male and female genitourinary system, and kidneys 31 , it is likely that the strong associations of WFDC2 with cardiac outcomes stem from peripheral organ responses rather than indicating direct cardiac dysfunction or vascular damage.…”
Section: Discussionmentioning
confidence: 95%
“…WFDC2 (also known as HE4)—a profibrotic protease inhibitor with a potential role in natural immunity 17 —emerged as the strongest proteomic predictor of heart failure. Previous research in hospitalized heart failure patients demonstrated associations of circulating WFDC2 with disease severity as well as kidney function 30 . As WFDC2 is expressed exclusively in non-cardiovascular tissues such as the respiratory tract, male and female genitourinary system, and kidneys 31 , it is likely that the strong associations of WFDC2 with cardiac outcomes stem from peripheral organ responses rather than indicating direct cardiac dysfunction or vascular damage.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that cardiac amyloidosis is associated with a high prevalence of AF [ 32 , 33 ]. A further study revealed that pathways of Aβ metabolic processes, Aβ formation and APP catabolic processes were activated in patients suffered from heart failure with concomitant AF [ 34 ], suggesting that Aβ deposition, as the marker of AD, also involved in pathophysiological processes of cardiac diseases. The pulmonary vein contains abundant amyloid peptides and directly influences atrial remodeling as a major substrate of AF [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The elevated protein biomarkers were assessed in pathways from the databases gene ontology (GO) biological processes, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Reactome pathways. 15 The statistical parameters applied were the hypergeometric test and the default Bonferroni step-down method for multiple testing corrections. The whole annotation option was used as a reference set, and only pathways with a corrected p-value ≤0.05 were considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…The overlapping common elevated protein biomarkers between the index and validation cohort were selected and further investigated in a pathway overrepresentation analysis, performed using the ClueGo plug‐in app (version 2.5.8) in Cytoscape (version 3.9.0), a software platform for visualizing biomolecular networks 13,14 . The elevated protein biomarkers were assessed in pathways from the databases gene ontology (GO) biological processes, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Reactome pathways 15 . The statistical parameters applied were the hypergeometric test and the default Bonferroni step‐down method for multiple testing corrections.…”
Section: Methodsmentioning
confidence: 99%